2019
DOI: 10.1016/j.rse.2019.111339
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hurricanes on the oceanographic conditions in the Exclusive Economic Zone of Cuba

Abstract: In this work, we analysed the satellite-based responses of sea surface temperature (SST) and chlorophylla (chl-a) concentration in the waters of the Exclusive Economic Zone (EEZ) of Cuba to hurricanes that crossed the EEZ between 1998 and 2016. We considered two spatial scales to capture the spatially heterogeneous nature of the effects of hurricanes. A first more fine-grained one where we considered 120 km radius disks centered at every consecutive hurricane position within the EEZ (scale 1) and a second more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 115 publications
3
6
0
Order By: Relevance
“…However, we found that the passage of a second TC disrupts these global patterns leading to a decreasing SST trend and a second chl-a bloom. This finding agrees with the one reported in Avila-Alonso et al (2019) for the waters surrounding Cuba since they found a progressive post-storm surface cooling during a month after the passage of hurricanes, which was partially determined by the passage of consecutive hurricanes across the study area. Moreover, extensive and long-lasting SST cooling as well as intense post-storm phytoplankton blooms after the passage of consecutive TCs have been documented in the northwestern Pacific Ocean (e.g., Wu and Li, 2018;Ning et al, 2019;Wang et al, 2020).…”
Section: Climatological Analysis Of Sea Surface Temperature and Chlorsupporting
confidence: 92%
See 2 more Smart Citations
“…However, we found that the passage of a second TC disrupts these global patterns leading to a decreasing SST trend and a second chl-a bloom. This finding agrees with the one reported in Avila-Alonso et al (2019) for the waters surrounding Cuba since they found a progressive post-storm surface cooling during a month after the passage of hurricanes, which was partially determined by the passage of consecutive hurricanes across the study area. Moreover, extensive and long-lasting SST cooling as well as intense post-storm phytoplankton blooms after the passage of consecutive TCs have been documented in the northwestern Pacific Ocean (e.g., Wu and Li, 2018;Ning et al, 2019;Wang et al, 2020).…”
Section: Climatological Analysis Of Sea Surface Temperature and Chlorsupporting
confidence: 92%
“…The higher chl-a concentration anomalies along the trajectory as compared the ones in the square study area from day -3 to 3 ( Figure 9A) are associated with both an increased upward displacement of D20 ( Figure 5B) and the horizontal advection of chl-a-rich waters from the coast of the northwestern Bahamas islands and the east coast of USA, which were impacted by Dorian (Avila et al, 2020). These higher chl-a concentration anomalies are consistent with the fact that surface phytoplankton blooms are common near the TC trajectory (e.g., Babin et al, 2004;Walker et al, 2005;Gierach and Subrahmanyam, 2008;Lin and Oey, 2016;Avila-Alonso et al, 2019).…”
Section: Chlorophyll-a Concentration Bloomsupporting
confidence: 69%
See 1 more Smart Citation
“…days −10 to −3 before hurricane passage) as a benchmark for comparison with the four post-storm weeks (i.e. from days 0 to 30, where day 0 refers to the day the hurricane entered the study area) in agreement with previous studies (Menkes et al, 2016;Avila-Alonso et al, 2019). For the square area, we considered day 0 as the day that Dorian started to impact it, i.e.…”
Section: Methodsmentioning
confidence: 94%
“…Hence, several studies have assessed the oceanic response to recent major hurricanes in the North Atlantic basin (e.g. Trenberth et al, 2018;Miller et al, 2019b;Avila-Alonso et al, 2020;Hernández et al, 2020) and others in very active hurricane seasons such as in 2005 (e.g. Oey et al, 2006Oey et al, , 2007Shi and Wang, 2007;Gierach and Subrahmanyam, 2008).…”
Section: Introductionmentioning
confidence: 99%